CYP1A2 genetic polymorphisms are associated with early antidepressant escitalopram metabolism and adverse reactions. (July 2013) - Kuo, Hsiang-Wei; Liu, Shu Chih; Tsou, Hsiao-Hui; Liu, Sheng-Wen; Lin, Keh-Ming; Lu, Shao-Chun; Hsiao, Mei-Chun; Hsiao, Chin-Fu; Liu, Chia-Yih; Chen, Chia-Hui; Lu, Mong-Liang; Shen, Winston W; et al.
Aim: The liver CYP1A2 enzyme may metabolize antidepressant escitalopram ( S -CIT) to S -desmethylcitalopram ( S -DCIT) and S -didesmethylcitalopram ( S -DDCIT). This study tested whether genetic polymorphisms in the CYP1A2 gene are associated with the treatment responses to S -CIT.Materials & methods: Ten SNPs in CYP1A2 were selected and genotyped in 158 patients under S -CIT treatment. The serum levels of S -CIT and its metabolites were measured by HPLC.Results: CYP1A2 SNPs rs2069521, rs2069526, rs4646425 and rs4646427 are significantly associated with the metabolic ratios of S -DDCIT/ S -DCIT (p = 0.002, 0.018, 0.008 and 0.004, respectively) at week 2 of treatment. Carriers of the allele types associated with higher S -DDCIT/ S -DCIT ratios had more severe side effects.Conclusion: These results suggest that genetic variants in CYP1A2 may be indicators for S -CIT metabolism and that the fast metabolizers may experience more severe adverse reactions in the early stages of S -CIT treatment. Original submitted 27 December 2012; Revision submitted 15 May 2013